Pengaruh Social Media Usage terhadap Conspicuous Online Consumption Dimediasi oleh Self-Image Congruity, dan Self-Esteem pada Kaum Milenial di Jabodetabek - Irsyad Muhammad Firdaus; Kurniawati Kurniawati; Nadhea Oudynella Marzia; Nindita Dwinurfrinda Putri; Radhita Intan Anggraini; Sela Kustiawan (Research Center and Case Clearing House PPM School of Management, 2023)
Social media usage and conspicuous online consumption for millennials are widely recognized in consumer research. This study aimed to analyze the effect of social media usage, self-image congruity, and self-esteem in conspicuous online consumption among millennials in Jabodetabek. The method in this study is quantitative, using survey research on all millennials in Jabodetabek as the object of research. Data collection is used by distributing questionnaires. The research sample was selected using purposive sampling, so 202 respondents were obtained for 2 weeks in June 2021. The data testing method was an instrument test with a validity and reliability test using SPSS. The data analysis method used Structural Equation Modeling (SEM) using AMOS software. The analysis results show a significant and positive relationship between social media usage, self-image congruity, self-esteem, and conspicuous online consumption. Self-image congruity and self-esteem are able to mediate between social media usage and conspicuous online consumption. Mid-luxury brand managers are advised to target this consumer group to increase conspicuous online consumption.